THERAPEUTICS PERSPECTIVES OF THE Hancornia speciosa GOMES: BIOACTIVE COMPOUNDS IN THE FRUIT, LEAVES, BARK AND LATEX - Pedrazini, Maria Cristina; dos Santos, Victor Augusto Benedicto; Groppo, Francisco Carlos (Revista Multidisciplinar em Saúde, 2022)
Introduction: Hancornia speciosa Gomes is a plant used in traditional Brazilian medicine. Its therapeutic activity can be explained by the presence of secondary metabolites. It is found in biomes such as the Amazon, Brazilian semiarid (caatinga), Atlantic forest and cerrado. The objective of this study was to review the literature, compiling information and identifying factors that influence its therapeutic activity as well as arousing interest in new studies. Methodology: The search included PubMed, Web of Science, Science Direct, Scielo, Medline and Google Scholar databases using the keywords “Hancornia speciosa Gomes”, “Natural Polymers”, “Mangaba”, “Magabeira”, “Chlorogenic acid”, “Rutin”, “Naringerin”, “Bornesitol”, “Hancornia Latex”, “Phytotherapy”, “Ethnopharmacology”, “Medicinal plants” and the relationship between them. The search was complemented by reading the referenced articles and updated until May 2022. Results: Due to its rich content of bioactive compounds, it may be a promising choice for nutraceuticals and therapeutics with anti-inflammatory, antibacterial, antihypertensive, gastroprotective, hepatoprotective, dermo protective, osteogenic and angiogenic properties. Conclusion: From a scientific point of view, it is necessary to standardize dosages, evaluate the pharmacodynamics, pharmacokinetics and toxicology, especially regarding the use of latex with the potential presence of pathogens in its composition. Randomized clinical studies based on the knowledge and popular use of this plant should be carried out after preclinical studies to prove its efficacy and safety.